Regulation of connective tissue growth factor gene expression in human skin fibroblasts and during wound repair. - Igarashi, A (1993)
Connective tissue growth factor (CTGF) is a cysteine-rich peptide that exhibits platelet-derived growth factor (PDGF)-like biological and immunological activities. CTGF is a member of a family of peptides that include serum-induced immediate early gene products, a v-src-induced peptide, and a putative avian transforming gene, nov. In the present study, we demonstrate that human foreskin fibroblasts produce high levels of CTGF mRNA and protein after activation with transforming growth factor beta (TGF-beta) but not other growth factors including PDGF, epidermal growth factor, and basic fibroblast growth factor. Because of the high level selective induction of CTGF by TGF-beta, it appears that CTGF is a major autocrine growth factor produced by TGF-beta-treated human skin fibroblasts. Cycloheximide did not block the large TGF-beta stimulation of CTGF gene expression, indicating that it is directly regulated by TGF-beta. Similar regulatory mechanisms appear to function in vivo during wound repair where there is a coordinate expression of TGF-beta 1 before CTGF in regenerating tissue, suggesting a cascade process for control of tissue regeneration and repair.